Managing Massive Time Series Streams with Multi-Scale Compressed Trickles - Reeves, Galen; Liu, Jie; Nath, Suman; Zhao, Feng (VLDB '2009: Proceedings of 35th Conference on Very Large Data Bases, 2009)
We present Cypress, a novel framework to archive and query massive time series streams such as those generated by sensor networks, data centers, and scientific computing. Cypress applies multi-scale analysis to decompose time series and to obtain sparse representations in various domains (e.g. frequency domain and time domain). Relying on the sparsity, the time series streams can be archived with reduced storage space. We then show that many statistical queries such as trend, histogram and correlations can be answered directly from compressed data rather than from reconstructed raw data. Our evaluation with server utilization data collected from real data centers shows significant benefit of our framework.